The propagation of chestnut (Castanea sativa Mill.) nodal explants - Gregor OSTERC; Marjeta ZAVRL FRAS; Tomaž VODENIK; Zlata LUTHAR (Acta Agriculturae Slovenica)
Chestnut is a woody species, which is difficult to propagate either generatively by seed or vegetatively by grafting or cuttings. The experiment of vegetative propagation included in vitro propagated shoots of the chestnut clone ‘Sobota’ from the northeast area of Slovenia. Propagation MS-½NO3 medium contained basic (macro- and microelements) MS medium with a half concentration of two nitrates (KNO3 and NH4NO3) and 100 mg/l inositol, 1 mg/l thiamine, 30 g/l sucrose, and 8 g/l agar. The propagation BW medium consisted of half strength broad leaved tree BT medium and half strength woody plant WP medium. Both propagation media contained 1 mg/l BAP (6-benzylaminopurine) or 1 mg/l zeatin. The in vitro shoots developed much better when propagated on medium containing BAP. With BAP irrespective of the medium, clusters developed significantly more shoots (average 2.1 per cluster) and showed a trend of more vigorous growth with the inclusion of BAP. Shoots grown on BW medium were of poorer quality, with high browning or necrosis and extremely highly intensive hyperhydration ratios.